American Association for Emergency Psychiatry Task Force on Medical Clearance of Adults - Eric L. Anderson; Kimberly Nordstrom; Michael P. Wilson; Jennifer M. Peltzer-Jones; Leslie Zun; Anthony Ng; Michael H. Allen (Western Journal of Emergency Medicine, 2017)
Introduction: In the United States, the number of patients presenting to the emergency department (ED) for a mental health concern is significant and expected to grow. The breadth of the medical evaluation of these patients is controversial. Attempts have been made to establish a standard evaluation for these patients, but to date no nationally accepted standards exist. A task force of the American Association of Emergency Psychiatry, consisting of physicians from emergency medicine and psychiatry, and a psychologist was convened to form consensus recommendations on the medical evaluation of psychiatric patients presenting to EDs. Methods: The task force reviewed existing literature on the topic of medical evaluation of psychiatric patients in the ED (Part I) and then combined this with expert consensus (Part II). Results: In Part I, we discuss terminological issues and existing evidence on medical exams and laboratory studies of psychiatric patients in the ED. Conclusion: Emergency physicians should work cooperatively with psychiatric receiving facilities to decrease unnecessary testing while increasing the quality of medical screening exams for psychiatric patients who present to EDs. [West J Emerg Med. 2017;18(2)235-242.]